The blended learning model from the perspective of cognitive load theory - Elena Viktorovna Evenko Elena Viktorovna; Olga Anatolievna Glivenkova; Olga Nikolaevna Morozova (Вестник Майкопского государственного технологического университета, 2023)
Blended learning model is based on cognitive load theory, which consists of three types: intrinsic, extraneous and germane and is connected to the working memory. Blended learning has recently become relevant. It is explained both by the need of the society for special technologies and forms of education, and by the development of new information technologies that makes it possible to consider the distance aspect of blended learning as a special autonomous technology with its own characteristics, standards and conceptual apparatus.The article analyzes the effects of blended learning model on the learner's cognitive load in order to solve the problem of cognitive overload. The purpose of the research is to establish the "knowledge-cognition" interaction process and to explore the control strategy of adequate cognitive load in the implementation of the blended learning model in connection with cognitive psychological processes.The method of theoretical analysis and pedagogical modeling has been used in the research. The foreign experience of using blended learning have been analyzed and pedagogical activity of the authors of the article has been reflected. The results show that the discrete knowledge can be transmitted to the learners through the structured knowledge presentation system after careful editing by an instructor-educator-designer, who affects the learning experience and the learning acquisition effect together with the digital educational environment and the learning task. It will become the mainstream direction of applied education and innovation in universities. Thus, a need for the emergence of a more flexible information educational environment is created, which allows students to gain knowledge anywhere, at any time and at their educational pace. At the same time, it is especially noted that the development of competencies of students only in distance learning format is more difficult than in the conditions of blended learning. Consequently, blended learning contributes to the development of student competencies due to a combination of various online technologie, which are aimed at the educational process.